Pengaruh Self Control dan Konformitas terhadap Perilaku Judi Online - Salsabila Syifa Ruswandi; Lilim Halimah (Bandung Conference Series: Psychology Science, 2024)
Abstract. The practice of online gambling in Indonesia is increasingly prevalent, with the Ministry of Communication blocking access to 499.645 gambling-related contents across various digital platforms. This includes a diverse range of people, including students, who are influenced by peer pressure and find it difficult to control themselves, leading to their involvement in online gambling. A study aimed to assess the influence of self-control and conformity on online gambling behavior among Muslim students. The research involved 124 Muslim students at the Islamic University of Bandung, selected through purposive sampling. The study utilized the Self Control Scale by Tangney, Baumeister, and Boone (2004), the conformity measurement by Putri (2018), and the Problem Gambling Severity Index (PGSI) developed by Ferris & Wyne (2001). The research employed a quantitative approach using multiple regression analysis to determine the partial and simultaneous effects of self-control and conformity on online gambling. The study found a significant partial influence of self-control on online gambling behavior with an R2 value of 0.138 and a sig value of 0.00, indicating 13.8% contribution of self-control to online gambling behavior. Additionally, there was a significant partial influence of conformity on online gambling behavior with an R2 value of 0.260 and a sig value of 0.00, signifying 26% contribution of conformity to online gambling behavior. The research revealed a simultaneous influence of self-control and conformity on online gambling behavior with an R2 value of 0.398 and a sig value of 0.00, demonstrating a combined contribution of 39.8% from both variables to online gambling behavior. These findings emphasize the importance of self-control and conformity in understanding and addressing online gambling behavior among Muslim students. Abstrak. Praktik judi online di Indonesia semakin marak beredar. Kementerian Komunikasi telah memutus akses 499.645 konten perjudian di berbagai platform digital. Terdapat berbagai kalangan masyarakat yang mengakses platform judi online, termasuk mahasiswa. Motif mahasiswa bermain judi online yaitu karena pengaruh teman sebaya di lingkungan sosialnya. Sulitnya mereka dalam mengontrol diri membuat mereka terlibat pada permainan judi online. Penelitian ini bertujuan untuk mengetahui pengaruh self control dan konformitas terhadap perilaku judi online pada mahasiswa muslim. Sampel penelitian sebanyak 124 mahasiswa muslim di Universitas Islam Bandung, yang didapat melalui teknik purposive sampling. Alat ukur yang digunakan adalah Self Control Scale yang dikonstruksi oleh Tangney, Baumeister dan Boone (2004), alat ukur konformitas yang dikonstruksikan oleh Putri (2018), dan alat ukur Problem Gambling Severity Index (PGSI) yang dikembangkan oleh Ferris & Wyne (2001). Metode kuantitatif dengan menggunakan teknik analisis regresi berganda digunakan untuk mengetahui pengaruh self control dan konformitas secara parsial dan simultan terhadap judi online. Hasil yang diperoleh secara parsial terdapat pengaruh yang signifikan self control terhadap perilaku judi online dengan nilai R2 = 0.138 nilai sig = 0.00 yang berarti self control berkontribusi derhadap perilaku judi online sebesar 13,8%. Terdapat pengaruh yang signifikan konformitas terhadap perilaku judi online dengan nilai R2 = 0.260. dan nilai sig = 0.00 artinya konformitas berkontribusi sebesar 26% terhadap perilaku judi online. Secara simultan, terdapat pengaruh self control dan konformitas terhadap perilaku judi online dengan nilai R2 = 0.398 dengan nilai sig = 0.00 artinya kedua variabel berkontribusi pada judi online sebesar 39,8%.